The Legal separation of women during the XVIII century in the tradition «El divorcio de la condesita» - Chilón Urribarri, Rut Bélen (2022)
This article will address, from the point of view of law, the most important legal cases to obtain a divorce, based on the history of the tradition «El divorcio de la condesita», a text that is part of the Tradiciones peruanas (Peruvian Traditions), by Ricardo Palma. We are interested in emphasizing, above all, the different civil laws that were published during the 18th century to win a divorce case presented by a woman. Likewise, we will analyze the differences between the legal norms required at that time to obtain a divorce, and those required nowadays.